Penerapan Qanun Jinayat di Aceh - Hudhaif Zuhdi Al-afify; Mu’min Firmansyah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The application of fiqih jinayah in Aceh is the implementation of Islamic criminal law regulated in Qanun Jinayat as part of the implementation of Islamic law in the region. This is based on the special authority granted by Law Number 11/2006 on the Government of Aceh. Qanun Jinayat includes various criminal provisions such as hudud, qisas, and ta'zir that regulate certain offenses, including zina, gambling, alcohol consumption, and khalwat. Punishments include flogging, fines, and imprisonment. However, the implementation of fiqh jinayah in Aceh faces various challenges, such as resistance from certain groups, limited public understanding, and issues of compatibility with human rights principles. On the other hand, this implementation is considered successful in reducing the level of certain crimes and strengthening the Islamic identity of the people of Aceh. Thus, fiqih jinayah in Aceh is an example of how Islamic law can be integrated into the national legal system, although it requires evaluation and adaptation to ensure its implementation is fair, transparent, and in accordance with the social context of the community.